(untitled) (Journal of the College of Basic Education, 2023)
God is the photographer. He created everything He created. He created man from clay and formed him as he wished. He mounted him in the best form and taught him to draw pictures, express through the picture, design the picture, read the picture, and taste the picture.The world is an image, life with all that is in it is an image, and all sciences are composite images. This is clearly evident as we receive and build our perceptions on countless visual and mental images, thus forming a comprehensive vessel for human culture and civilization. In the last two decades, the perceived visual image has become the most important component and the source of action and response. Human action Modern technologies have enhanced the means of communication and its contemporary tools, what has become called the culture of the image in various fields.The artistic image constitutes, in contemporary history, an intellectual and cultural state that touches the educational, social and human reality in techniques that have made the human society a more close society despite the difference in its issues and the contradiction of its goals. About human capabilities, might, hopes and aspirations. Man has been able, through contemporary technologies, to make the artistic image a means of education, education, media, marketing, and a communication tool. Despite the expansion of the roles of the image and its effects, these roles are still fertile material for research, analysis and discovery with an infinite perspective as a visual perception that stimulates the internal perception that explains its existence (the image) to produce cumulative values that form the consciousness of individuals and groups and influence their decisions.And the image is stored as a real material within it the real and imaginary sensibilities, the perceived and the unaware of them, which have been formed from human experiences over the ages in fixed and transformed formulas and in spontaneous and intentional formations that affect ideas and give cultures their characteristics and extend their potential energies.The culture of the artistic image is an important part of the general culture constituting the culture of society, which affects its characteristics and characteristics in the type and nature of visual culture and provides it with the elements of its growth and development. etc...).This research comes out of a sense of the importance of the image and its cultural and artistic connections with its influential human interactions and an explanation of the extension of its social and educational effects.